Collective Optical, FTIR, and Photoluminescence Spectra of CeO2 and/or Sm2O3-Doped Na2O–ZnO–P2O5 Glasses - M. A. Marzouk; H. A. ElBatal; Y. M. Hamdy; F. M. Ezz-Eldin (International Journal of Optics)
Glasses with the Na2O–ZnO–P2O5 composition and doped with single CeO2, Sm2O3, or mixed dopants were melted and studied. Collective optical, photoluminescence, and FT-infrared spectral studies were carried out. CeO2-doped glasses show two extra UV absorption bands due to Ce4+ and Ce3+ ions while Sm2O3-doped samples reveal pronounced peaks collected into two segments from 367 to 472 nm and from 950 to 1623 nm which are characteristic of absorption from Sm3+ ions. The mixed dopants glasses show combined UV-visible–near-IR absorption peaks due to cerium (Ce4+, Ce3+) ions and samarium (Sm3+) ions. The photoluminescence spectra (PL) of the single CeO2-doped and Sm2O3-doped glasses and even the mixed dopant sample reveal luminescence spectra after excitation which are characteristic of the rare-earth ions. The intensities for both excited or emitted peaks are found to increase with the increase of the rare-earth percent. FTIR spectra of the glasses show pronounced vibrational peaks related to phosphate groups (Q2 and Q3 units) in accordance with the P2O5 percent (70 mol %).